(untitled) (LEARNing Landscapes, 2008)
The author examines the role that high school physical activities have played in shaping her as person and, ultimately, as a leader. She provides insights on not just her passion and dedication for sports, but also on a sense of accomplishment, a desire to learn, inspiration, teamwork and the joy of mentoring younger student athletes—all invaluable building blocks for leadership.